Bayesian and E-Bayesian estimation for the Kumaraswamy distribution based on type-ii censoring - Reyad, Hesham; Ahmed, Soha Othman (International Journal of Advanced Mathematical Sciences, 2016)
This paper introduces the Bayesian and E-Bayesian estimation for the shape parameter of the Kumaraswamy distribution based on type-II censored schemes. These estimators are derived under symmetric loss function [squared error loss (SELF))] and three asymmetric loss functions [LINEX loss function (LLF), Degroot loss function (DLF) and Quadratic loss function (QLF)]. Monte Carlo simulation is performed to compare the E-Bayesian estimators with the associated Bayesian estimators in terms of Mean Square Error (MSE).